High resolution structural studies of membrane proteins using solid state NMR - Aslimovska, L (2008)
NMR crystallography is a new and developing area. Unlike solution state NMR, solid state NMR has the potential for structural studies of large, motionally restricted biological macromolecules, such as proteins in crystals which may, or may not, diffract. However, finding the best and the most useful sample form and geometry is still a major obstacle to rapid progress. Little has been reported about protein sample preparation for any class of protein for NMR crystallography, mainly since the availability of NMR labelled proteins is still not routine, especially for eukaryotic membrane proteins. The amino acid L-glutamate is the major excitatory neurotransmitter in the brain. Details of glutamate binding to any of its main brain or sensory receptors are not well resolved at the atomic level. In an effort to resolve the glutamate binding mechanism by solid state NMR methods, full-length taste and brain mGluR4 were expressed in E. coli, but proved to be toxic for the cells. The ligand-binding domains (LBD) of mGluR4, with various fusions for the periplasmic expression and with various fusions for expression in the cytoplasm therefore, were used. Solubilisation and then purification of the LBD from inclusion bodies is still under way, no crystals of mGluR4 for NMR were, therefore, grown. Initial NMR spectra of labelled 13C, 15N and 17O glutamate have been recorded to verify sensitivity requirements. Using homology modelling, a model for the truncated version of the ligand binding domain of mGluR4 has been constructed as a basis for designing solid state NMR experiments to probe the ligand binding site in the receptor. Bacteriorhodopsin is a large membrane protein and a model for G-protein coupled receptors (GPCRs). Spectra of bacteriorhodopsin produced in H. salinarium in purple membrane are reported here and compared to spectra of the protein crystallised from bicelles. Optimal conditions for producing spectra suitable for spectral assignment are reported as an initial step towards spectral resolution. Three differently labelled samples of bacteriorhodopsin were prepared to test the applicability of the various assignment strategies and the effects of deuteration on quality of solid state NMR spectra of a large, crystalline membrane protein.